2016
DOI: 10.1111/bcp.13020
|View full text |Cite
|
Sign up to set email alerts
|

Palmitoylethanolamide for the treatment of pain: pharmacokinetics, safety and efficacy

Abstract: Palmitoylethanolamide (PEA) has been suggested to have useful analgesic properties and to be devoid of unwanted effects. Here, we have examined critically this contention, and discussed available data concerning the pharmacokinetics of PEA and its formulation. Sixteen clinical trials, six case reports/pilot studies and a meta‐analysis of PEA as an analgesic have been published in the literature. For treatment times up to 49 days, the current clinical data argue against serious adverse drug reactions (ADRs) at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
127
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(129 citation statements)
references
References 55 publications
0
127
0
2
Order By: Relevance
“…PEA (N-2-hydroxyethyl) hexadecamide, palmidrol belongs to the family of N-acylethanolamines and is an active anti-inflammatory agent. 15 There is evidence that PEA has analgesic proprieties without side effects in humans. 15 In an animal study, PEA was administered in combination with tramadol showing its enhanced analgesic efficacy also at lowdoses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…PEA (N-2-hydroxyethyl) hexadecamide, palmidrol belongs to the family of N-acylethanolamines and is an active anti-inflammatory agent. 15 There is evidence that PEA has analgesic proprieties without side effects in humans. 15 In an animal study, PEA was administered in combination with tramadol showing its enhanced analgesic efficacy also at lowdoses.…”
Section: Resultsmentioning
confidence: 99%
“…15 There is evidence that PEA has analgesic proprieties without side effects in humans. 15 In an animal study, PEA was administered in combination with tramadol showing its enhanced analgesic efficacy also at lowdoses. 16 Rosemary, Rosmarinus (R.) officinalis L. has analgesic, anti-inflammatory and anti-neurodegenerative properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PEA is a member of the fatty‐acid ethanolamide family described in 1957, which is synthetized from the common phospholipid precursor of anandamide (endocannabinoid acting on CB 2 receptors) and therefore is thought to potentiate the action of endocannabinoids to reduce pain and inflammation . Its evaluation in the treatment of neuropathic pain had already begun in 1975, and preclinical studies point out how PEA can be effective in several models of pain including sciatic nerve ligature of neuropathic pain, although it has no action in acute thermal pain . PEA does not display a unique biochemical mechanism, and many biological targets are able to evocate its pharmacological response .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to drugs interacting with the EC system, PEA has been widely investigated as an additive during various chronic pain conditions such as FM. Currently, PEA is marketed as a nutraceutical (Normast™, Pelvilen™, and PeaPure™ ) in some European countries (e.g., Italy and Spain) and is used as a food supplement in other countries (e.g., Netherlands) [143]. A meta-analysis of twelve studies showed that PEA elicits a progressive reduction of pain intensity significantly higher than controls and the PEA effects were independent of patient age or gender and not related to the type of chronic pain [144].…”
Section: Ec System and Naes In Human Pain Studiesmentioning
confidence: 99%